Матрична еволюційна нейро-фаззи система для швидкого розпізнавання образів-зображень - Чала, О. С. (ХНУРЕ, 2020)
In this thesis the task of data stream fuzzy classification that is fed to processing in online mode wherein the characteristics of the data can be changed in time in an unpredictable way. For the solution the evolving fuzzyprobabilistic neural network for fast image processing is proposed. Distinctive features of the system are, firstly, the data are fed to the network in matrix form, secondly, in process of learning the architecture of neural network, activation function parameters including centroids and width parameters tune which significantly raise the accuracy